The history of the Society of Jesus in Colombia, 1844-1861 - Martinez, J; Jorge Enrique Salcedo Martinez, S.J. (2011)
This thesis examines the activity of the Jesuits in Colombia during the nineteenth century; it demonstrates how their return to the country in 1844 became a highly controversial political issue until 1884, when the national government authorized their permanent residence. The Jesuits were established in the country from 1844 to 1850, and then from 1858 to 1861. These two short sojourns generated significant debate between the Conservative and Liberal parties. The first return of the Jesuits coincided with the formation of these two parties and the debate over the separation of Church and State. It was after the Guerra de los Supremos, with the defeat of the Liberal Party and victory for the Conservative Party, that the latter passed a law on mission schools that allowed the return of the Society after its exile during colonial times. The Liberals considered the law of April 1842 to be a tactic used by the Conservatives to empower their political project, and when the Jesuits arrived in the country, the Liberal Party started a campaign against them in Congress and through the press. As the invitation for their return to New Granada had been issued by the Conservative government, Liberals considered them to be allies of the Conservatives and deserving of their political antipathy. The decrees issued regarding the return of the Jesuits clearly stated that they were to be assigned to Colegios de Misiones and Casas de Escala (Rest Residences) in mission territories. The Superior General of the order in Rome and the ecclesiastical authorities in Colombia interpreted the law as justifying the work of the Jesuits in establishing missions among the indigenous people and also in education in general. Eladio Urisarri, the official in Rome in charge of arranging the return of the Jesuits, supported this interpretation, but the latent ambiguity was a continual issue. The thesis analyses these episodes within the context of the republic’s politics and the state of the Colombian Church at the time, and examines the Jesuits’s experiences in Bogotá and the other dioceses where they were present.